2016
DOI: 10.1039/c6ob01938b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 28a-homoselenolupanes and 28a-homoselenolupane saponins

Abstract: A practical synthesis of 28a-homo-28a-selenolupane triterpenes and the corresponding selenosaponins containing d-mannose, l-arabinose, l-rhamnose, and d-idose moieties is described. Selenium containing triterpenes were obtained from the readily available 3-O-allyl-homobetulin mesylate by nucleophilic substitution with the selenocyanate ion which upon reduction of the -SeCN group afforded the free selenol. Glycosylation using classical Schmidt donors gave 1,2-trans selenosaponins as the main product as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…They do this apoptotic activity through mechanism encompassing both microtubule and Akt inhibition (Krishnegowda et al 2011). A compound selenocyanate containing triterpenes based on homobetulin scaffold was developed and showed antiproliferative activity in the low µM range against non-tumor cells (Sidoryk et al 2016).…”
Section: Selenocyantesmentioning
confidence: 99%
“…They do this apoptotic activity through mechanism encompassing both microtubule and Akt inhibition (Krishnegowda et al 2011). A compound selenocyanate containing triterpenes based on homobetulin scaffold was developed and showed antiproliferative activity in the low µM range against non-tumor cells (Sidoryk et al 2016).…”
Section: Selenocyantesmentioning
confidence: 99%
“…Selenoglycosides comprise a subset of selenium‐containing compounds and are known to possess a diverse set of useful biological activities (Figure ). Their potential application in the development of novel carbohydrate‐based therapeutics is suggested by their anti‐metastatic ( 1 ), immunostimulatory ( 2 ), and anti‐tumor activities. Additionally, selenoglycosides demonstrate their utility as probes for studying carbohydrate–protein interactions .…”
Section: Figurementioning
confidence: 99%
“…Recently, Baran and co-workers have developed a late-stage diversication approach for improving the pharmacokinetic properties of BA via C-H oxidation through a combination of chemical and enzymatic reactions. 11 In parallel to these pioneering studies, we 1,12-18 and others [19][20][21][22][23] have been interested in coupling diverse hydrosoluble sugar moieties at the C-3 and/or C-28 positions of BA and other members of the lupane-type triterpenoid family such as betulin and lupeol. Among other things, we have shown that synthetic BA saponins bearing L-rhamnopyranose (Rha) residues at the C-3 position were potent cytotoxic agents 15 devoid of hemolytic activity 12 as compared to oleanane-type saponins.…”
Section: Introductionmentioning
confidence: 99%